Can risk groups accurately predict non‐sentinel lymph node metastasis in sentinel lymph node‐positive endometrial cancer patients? A Turkish Gynecologic Oncology Group Study (TRSGO‐SLN‐004). Issue 2 (1st December 2020) - Altin, Duygu; Taskin, Salih; Tokgozoglu, Nedim; Vatansever, Dogan; Guler, Adbul H.; Gungor, Mete; Tasci, Tolga; Turan, Hasan; Kahramanoglu, Ilker; Yalcin, Ibrahim; Celik, Cetin; Kose, Faruk; et al.
Abstract: Background and Objectives: The purpose of this study was to find out the risk factors associated with non‐sentinel lymph node metastasis and determine the incidence of non‐sentinel lymph node metastasis according to risk groups in sentinel lymph node (SLN)‐positive endometrial cancer patients. Methods: Patients who underwent at least bilateral pelvic lymphadenectomy after SLN mapping were retrospectively analyzed. Patients were categorized into low, intermediate, high‐intermediate, and high‐risk groups defined by ESMO‐ESGO‐ESTRO. Results: Out of 395 eligible patients, 42 patients had SLN metastasis and 16 (38.1%) of them also had non‐SLN metastasis. Size of SLN metastasis was the only factor associated with non‐SLN metastasis ( p  = .012) as 13/22 patients with macrometastasis, 2/10 with micrometastasis and 1/10 with isolated tumor cells (ITCs) had non‐SLN metastasis. Although all 4 metastases (1.8%) among the low‐risk group were limited to SLNs, the non‐SLN involvement rate in the high‐risk group was 42.9% and all of these were seen in patients with macrometastatic SLNs. Conclusions: Non‐SLN metastasis was more frequent in higher‐risk groups and the risk of non‐SLN metastasis increased with the size of SLN metastasis. Proceeding to complete lymphadenectomy when SLN is metastatic should further be studied as the effect of leaving metastatic non‐SLNs in‐situ is not known.